Análise dos parâmetros de conforto térmico em habitações populares de um conjunto em João Pessoa/ PB. - Silva, Nayane Laurentino da (2015)
The search for mild conditions for users of buildings not air-conditioned, especially residential is of paramount importance in hot and humid regions. Climatic factors represent major influence on environmental projects built for getting the comfort of its occupants and efficiency in energy consumption. The research is meant to examine the parameters of thermal comfort in affordable housing a set in Singapore and the relationship of each of the comfort indices PMV and PPD, this because the thermal conditions under which the inhabitants are subjected may exercise great influence on their behavior, reactions and health. The research is descriptive, with a quantitative and qualitative approach, using data collected inside the residence, based on the ISO 7730/2005, to analyze the environment by means of statistical techniques and computational resources. The housing Anayde Beiriz, chosen for study, is situated in the neighborhood of Industries in the city of João Pessoa / Paraíba. The assessed apartments have different orientations according to their location on the ground; addition to situate on the last floor and the ends of each block. The sample consisted of 19 apartments of which data were collected from 8h to 17h in the days selected using the equipment called, Heat Stress Meter (TGD 300). With the data a statistical analysis was performed to identify which parameters have most influence on thermal comfort those affordable housing. The results showed the thermal behavior within the evaluated units that resulted in high temperatures analyzed in the winter and summer periods. It was concluded that the personal and climatic variables, involving the parameters of thermal comfort, have correlation with the wind chill into the housing having high correlation to air temperature and low correlation thermal resistance of clothing. All units showed thermal discomfort with the PMV values above 0.5, ranking environments as slightly warm or hot in most of the evaluated times, with the PPD index greater than 10% in both periods studied. - Winter and Summer Yet in the winter for a few hours of the morning period showed sensation of thermal comfort, with the lowest PPD index or equal to 10%, with a tendency that feeling also occur at night.